The association between diuretic class exposures and enteral electrolyte use in infants developing grade 2 or 3 bronchopulmonary dysplasia in United States children’s hospitals - Nelin, Timothy D.; Lorch, Scott; Jensen, Erik A.; Alexiou, Stamatia; Gibbs, Kathleen; Napolitano, Natalie; Monk, Heather M.; Furth, Susan; Shults, Justine; Bamat, Nicolas A. (Journal of perinatology, 2021)
Objective To evaluate the association between chronic diuretic exposures and enteral electrolyte use in infants developing severe bronchopulmonary dysplasia (sBPD). Study design Retrospective longitudinal cohort study in infants admitted to United States children’s hospitals. We identified diuretic exposures and measured enteral NaCl and KCl use during pre-defined exposure risk-interval days. We used mixed-effects logistic regression to model the association between diuretic exposures and electrolyte use. Results We identified 442,341 subject-days in 3252 infants. All common diuretic classes and class combinations were associated with increased NaCl and KCl use. Thiazide monotherapy was associated with greater electrolyte use than loop monotherapy. The addition of potassium-sparing diuretics was associated with a limited reduction in KCl use compared to thiazide monotherapy. Conclusions Chronic diuretic exposures are associated with increased NaCl and KCl use. Presumptions about the relative impact of different diuretic classes on electrolyte derangements may be inaccurate and require further study.